Asymmetric Disulfanylbenzamides as Irreversible and Selective Inhibitors of Staphylococcus aureus Sortase A. (25th March 2020) - Barthels, Fabian; Marincola, Gabriella; Marciniak, Tessa; Konhäuser, Matthias; Hammerschmidt, Stefan; Bierlmeier, Jan; Distler, Ute; Wich, Peter R.; Tenzer, Stefan; Schwarzer, Dirk; Ziebuhr, Wilma; Schirmeister, Tanja
Abstract: Staphylococcus aureus is one of the most frequent causes of nosocomial and community‐acquired infections, with drug‐resistant strains being responsible for tens of thousands of deaths per year. S. aureus sortase A inhibitors are designed to interfere with virulence determinants. We have identified disulfanylbenzamides as a new class of potent inhibitors against sortase A that act by covalent modification of the active‐site cysteine. A broad series of derivatives were synthesized to derive structure‐activity relationships (SAR). In vitro and in silico methods allowed the experimentally observed binding affinities and selectivities to be rationalized. The most active compounds were found to have single‐digit micromolar K i values and caused up to a 66 % reduction of S. aureus fibrinogen attachment at an effective inhibitor concentration of 10 μM. This new molecule class exhibited minimal cytotoxicity, low bacterial growth inhibition and impaired sortase‐mediated adherence of S. aureus cells. Abstract : Don't get too attached : Transforming the warhead from benzisothiazolinone to disulfanylbenzamide and systematic structure‐activity relationship studies have uncovered novel S. aureus sortase A inhibitors with potent inhibition of fibrinogen attachment. The mode of action was identified as the transfer of a thioalkyl fragment to Cys126. Fine‐tuning the warhead reactivity yielded inhibitors with selectivity over other cysteine proteases.